Corpo, gênero e identidade: experiências transgênero na cidade de Manaus Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This paper aims to discuss the relationship and the links between gender identity, body and performativity through an ethnography that took place in the city of Manaus. The interlocutors of this research are transgender women and men of various ages, mostly from an urban and educated middle class. After a theoretical and terminogical review, we discuss some issues related to technologies that support the creation and reproduction of gender and its performativity, as well as practices that form the bodies and speeches that deny their right to be, through transphobia.
Keywords: Transgeneridade; Performatividade; Transfobia; CIÊNCIAS HUMANAS: ANTROPOLOGIA